A direct assay of carboxyl-containing small molecules by SALDI-MS on a AgNP/rGO-based nanoporous hybrid film. Issue 9 (7th January 2016) - Hong, Min; Xu, Lidan; Wang, Fangli; Geng, Zhirong; Li, Haibo; Wang, Huaisheng; Li, Chen-zhong
Abstract : Here we prepared a nanoporous multilayer film for the direct analysis of carboxyl-containing small molecules by surface-assisted laser desorption/ionization mass spectrometry with silver nanoparticles and reduced graphene oxide through layer-by-layer electrostatic self-assembling. Abstract : Silver nanoparticles (AgNPs) and reduced graphene oxide (rGO) hybrid nanoporous structures fabricated by the layer-by-layer (LBL) electrostatic self-assembly have been applied as a simple platform for the rapid analysis of carboxyl-containing small molecules by surface-assisted laser desorption/ionization (D/I) mass spectrometry (SALDI-MS). By the simple one-step deposition of analytes onto the (AgNP/rGO)9 multilayer film, the MS measurements of various carboxyl-containing small molecules (including amino acids, fatty acids and organic dicarboxylic acids) can be done. In contrast to other energy transfer materials relative to AgNPs, the signal interferences of a Ag cluster (Ag n + or Ag n − ) and a C cluster (C n + or C n − ) have been effectively reduced or eliminated. The effects of various factors, such as the pore structure and composition of the substrates, on the efficiency of D/I have been investigated by comparing with the (AgNP)9 LBL nanoporous structure, (AgNP/rGO)9 /(SiO2 NP)6 LBL multilayer film and AgNP/prGO nanocomposites.